2013
DOI: 10.1161/circheartfailure.112.000196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early, Late, and Long-term Nonselective β-Blockade on Left Ventricular Remodeling, Function, and Survival in Chronic Organic Mitral Regurgitation

Abstract: Background-Mitral regurgitation (MR) produces sympathetic nervous system activation which is detrimental in other causes of heart failure. However, whether β-blockade is beneficial in MR has not been determined. Methods and Results-Eighty-seven rats with significant organic MR were randomized to the β-blockade group (n=43) or the control group (n=44). Carvedilol was started in week 2 post MR induction and given for 23 to 35 weeks in the β-blockade group. Echocardiography was performed at baseline and at weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The acuity and severity of surgically created MR in animal models versus the physiological response to chronic and gradually worsening MR in humans, along with differences in heart rate response and the use of different beta-blockers in different studies, had precluded firm conclusions on the utility of beta-blockers in this clinical setting [20]. In this context, our study provides insight into the effects of beta-blockers among initially asymptomatic patients with chronic severe nonischemic MR. Our data are consistent with previous studies which suggested an increase in LV dimension with use of beta-blockers [12,17,19], which could accelerate the development of commonly accepted indications for mitral valve surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The acuity and severity of surgically created MR in animal models versus the physiological response to chronic and gradually worsening MR in humans, along with differences in heart rate response and the use of different beta-blockers in different studies, had precluded firm conclusions on the utility of beta-blockers in this clinical setting [20]. In this context, our study provides insight into the effects of beta-blockers among initially asymptomatic patients with chronic severe nonischemic MR. Our data are consistent with previous studies which suggested an increase in LV dimension with use of beta-blockers [12,17,19], which could accelerate the development of commonly accepted indications for mitral valve surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, subsequent studies failed to support a reduction in LV volumes with beta-blockade [15,17]. On the contrary, in an animal model of surgically induced MR, a reduction in heart rate associated with the use of nonselective beta-blockade with carvedilol resulted in significantly decreased LVEF and increased LV volumes and mortality [12,13]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal models of chronic MR, beta blockade improves intrinsic contractile function of isolated cardiomyocytes and increases contractile elements 88, 89 . However, disturbingly, in a recent study of rodents with surgically-induced MR, carvedilol-mediated reduction in heart rate resulted in significant decrease in LVEF, increase in LV volumes and, most importantly, increase in mortality compared with no therapy 90, 91 .…”
Section: Beta Blockersmentioning
confidence: 99%